Optimization of a new multi-reagent procedure for quantitative mussel digestion in microplastic analysis. (December 2021) - Fraissinet, Silvia; Pennetta, Antonio; Rossi, Sergio; De Benedetto, Giuseppe E.; Malitesta, Cosimino
Abstract: Over the last few years, different digestion protocols have been proposed to extract microplastics from mussels, an important product from aquaculture and a relevant economic resource, always scrutinized as a potential pollutant concentrator. In this study, a full factorial experimental design technique has been employed to achieve efficiency in removing biological materials while maximizing the recoveries of five common microplastics (polyethylene, polystyrene, polyethylene terephthalate, polypropylene and polyamide). A robust setpoint was calculated, 2.5% potassium hydroxide at 60 °C for 3 h with 5% hydrogen peroxide and 2.7% of methanol, permitting the quantitative digestion of mussel tissues and recovery of microplastics. These experimental conditions were successfully used to digest whole mussels bought from a local market, which possess high levels of microplastic contamination (41 items/g dry weight). The results highlight the importance of optimizing protocols to develop robust, easy to use and cheap quantitative approaches for analysing microplastic accumulation in edible organisms. Graphical abstract: Unlabelled Image Highlights: Multireagent mixture designed to enhance mussel tissue digestion. Simultaneous optimization of both digestion efficiency and plastic recovery. The procedure is robust, fast, easy to scale-up and cost effective Raman spectroscopy showed no polymer modifications using the optimal digestion procedure.